Peningkatan Kesadaran Hukum Masyarakat Desa Cengal dalam Pencegahan Tindak Pidana Narkotika - Gladystia Nirwana Mulyaputri; Novia Andini; Pipin Apriani; Rian Juliansyah Pratama; Veggy Juniwati; Iman Jalaludin Rifa’i; Haris Budiman; Erga Yuhandra; Suwari Akhmaddhian (Empowerment : Jurnal Pengabdian Masyarakat, 2025)
Narcotics abuse is a national problem that is considered serious by the government and can cause damage to the morals of a nation. In Indonesia, narcotics abuse is increasing over time. Narcotics abuse has a negative impact on both dealers and users, both physically and psychologically. This is what creates a sense of vigilance in the community, to always make the best efforts to prevent the distribution and use of narcotics at various levels. Therefore, education is needed to increase legal knowledge and understanding through legal counseling to the community. The aim of this legal counseling activity is to increase public legal awareness. This legal counseling effort was carried out in Cengal Village, Japara District, Kuningan Regency, which was held on January 30 2024. This event was opened with a speech from a Lecturer at the Faculty of Law, Kuningan University to convey the aims and objectives of carrying out this event and was continued by a speech from the head of Cengal Village or others. represents it as a welcome greeting. This agenda was carried out as an effort to provide understanding and to increase awareness among the community and village officials about the dangers of drugs which are becoming more common every day as well as legal assistance for people who need legal assistance services at the Faculty of Law, Kuningan University, namely PKBH or Legal Assistance and Consultation Center.